2019
DOI: 10.1038/s41419-019-1543-z
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 signaling and autophagy are complementary in protecting lipopolysaccharide/d-galactosamine-induced acute liver injury by licochalcone A

Abstract: Licochalcone A (Lico A), isolated from Xinjiang licorice Glycyrrhiza inflate, has been shown to have antioxidative potential via the activation of nuclear factor-erythroid 2-related factor 2 (Nrf2) activation, which is involved in the prevention of acetaminophen-induced hepatotoxicity. The purpose of the current study was to further explore the protective effect of Lico A against lipopolysaccharide/d-galactosamine (LPS/GalN)-induced acute liver injury (ALI) and its underlying molecular mechanisms. Our results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 48 publications
1
64
0
Order By: Relevance
“…In the CCl 4 + bicyclol 48 h group, the expression level of p-mTOR/mTOR decreased to approximately 43.6% and 72.3% that of the control and CCl 4 exposure group, respectively. The MAPK, including the c-Jun NH2-terminal kinase (JNK), ERK, and p38, has been considered the main signaling pathway relevant to acute inflammation, which is also involved in the process of autophagy and anti-oxidant activities (Song et al, 2015;Lv et al, 2019). Our results showed that respective level of p-JNK/JNK protein expression increased 1.7-fold at 48 h, p-ERK/ERK and p-p38/p38 increased 1.7-fold and 1.7-fold at 24 h CCl 4 exposure, but bicyclol treatment effectively inhibited MAPK phosphorylation, indicating multiple responses and pathways may be responsible for bicyclol-mediated hepatoprotective effect.…”
Section: Groupmentioning
confidence: 99%
“…In the CCl 4 + bicyclol 48 h group, the expression level of p-mTOR/mTOR decreased to approximately 43.6% and 72.3% that of the control and CCl 4 exposure group, respectively. The MAPK, including the c-Jun NH2-terminal kinase (JNK), ERK, and p38, has been considered the main signaling pathway relevant to acute inflammation, which is also involved in the process of autophagy and anti-oxidant activities (Song et al, 2015;Lv et al, 2019). Our results showed that respective level of p-JNK/JNK protein expression increased 1.7-fold at 48 h, p-ERK/ERK and p-p38/p38 increased 1.7-fold and 1.7-fold at 24 h CCl 4 exposure, but bicyclol treatment effectively inhibited MAPK phosphorylation, indicating multiple responses and pathways may be responsible for bicyclol-mediated hepatoprotective effect.…”
Section: Groupmentioning
confidence: 99%
“…*p < 0.05 and **p < 0.01 vs. WT control group; # p < 0.05 and ## p < 0.01 vs. WT APAP group; † p < 0.05 and † † p < 0.01 vs. NFE2L2 −/− control group; § p < 0.05 and § § p < 0.01 vs. NFE2L2 −/− APAP group. permeability, massive neutrophil infiltration, and release of inflammatory mediators (Lv et al, 2019). Our results indicated that APAP significantly increased mortality, serum activities of ALT and AST, and severity of histopathological changes in the liver.…”
Section: Discussionmentioning
confidence: 50%
“…Fan et al, in their original research article, report on isoorientin-mediated suppression of APAP-induced hepatotoxicity in mice via activation Nrf2 anti-oxidative pathway and the involvement of AMPK/Akt/GSK3b signaling. This hepatoprotective effect of isoorientin could be mediated by autophagy activation, as reported by others (Muhammad et al, 2018;Lv et al, 2019). The last article by Zhang et al conclude that salvianolic acid B inhibits activation of human primary hepatic stellate cells through downregulation of MEF2 (myocyte enhancer factor 2) signaling pathway, resulting in subsequent amelioration of stellate cellmediated hepatic fibrosis.…”
mentioning
confidence: 56%